Tracking global health communication publication trends - Fitri Hardianti; Benni Handayani; Arif Ardi Wibowo (Jurnal Studi Komunikasi, 2024)
The field of communication has evolved and become more diverse, leading to the emergence of health communication as a multidisciplinary field of study. This study aims to identify several studies that examine the patterns and distinctiveness of health communication research globally and present them visually. The method used is a quantitative paradigm with a bibliometric approach. A total of 1,639 documents will be analysed from the search through Scopus obtained from several specific criteria. The results showed that over the past five years (2019-2023), the increase in the growth of the number of publications related to health communication amounted to 14.07%. The results of the analysis also show Health communication as the source with the most relevant and highest publications totalling 256 articles. The authors who produce the most publications related to this topic include Kim S and Noar SM with 13 articles each. Meanwhile, the country that produces the most correspondence authors and the highest citations is the USA with a total of 787 articles. The most popular keyword is health communication with a frequency of 650 mentions. This analysis also provides a roadmap for future research in health communication, highlighting untapped areas and encouraging global collaboration in this field.